Hemodynamic Resuscitation Characteristics of Emergency Department Patients with Sepsis and Hypotension who are and are not Admitted to ICU; a Prospective Cross-sectional Study - Vella, Rebecca; Jones, Philip; Keijzers, Gerben (Archives of Academic Emergency Medicine, 2024)
Introduction: There is an evidence–practice gap in the optimal timing and volume of intravenous fluid as well as vasopressor administration in managing patients with sepsis. This study aimed to explore current hemodynamic resuscitation practice in emergency department (ED) for patients with sepsis and hypotension. Methods: This is a sub-analysis of the prospective multicentre ARISE FLUIDS observational study, which was conducted in 70 EDs across Australia and New Zealand. Baseline characteristics, as well as ED management and outcome of sepsis patients were compared between patients who were and were not admitted to intensive care unit (ICU) or high dependency unit (HDU). Results: A total of 587 patients with a median age of 65 years and even sex distribution (49% female) were available for analysis. Almost two-thirds of patients with sepsis (63.2%, n=371) were not admitted to ICU/HDU and were given lower intravenous (IV) fluid volumes over 24-hours, compared to those receiving critical care (4077ml vs. 5421ml, p<0.001). Patients not admitted to an ICU/HDU had a lower Acute Physiology And Chronic Health Evaluation (APACHE) II score (median 14 vs. 18, P<0.001) and serum lactate level (1.8 vs. 2.8 mmol/L, P<0.001) compared to those admitted to ICU/HDU and 5.9% received a vasopressor infusion in the first 24-hours. Females, patients aged <65 years, and those with urosepsis or sepsis of non-respiratory origin received a greater volume of IV fluids. Conclusion: Almost two-thirds of patients were not admitted to ICU/HDU. In patients not admitted to ICU/HDU, 1 in 17 received a vasopressor infusion during their ED or early hospital stay. Patients not admitted to ICU/HDU received less fluid in the first 24 hours than those who were. Greater resuscitation fluid volumes were independently associated with female sex, age <65 years, higher lactate levels, and urinary or non-respiratory source of sepsis.